CD44 expressed by myeloid cells promotes glioma invasion - Ivanova, Ekaterina L.; Costa, Barbara; Eisemann, Tanja; Lohr, Sabrina; Boskovic, Pavle; Eichwald, Viktoria; Meckler, Jasmin; Jugold, Manfred; Orian-Rousseau, Veronique; Peterziel, Heike; Angel, Peter (Frontiers in Oncology, 2022)
Glioblastoma multiforme (GBM) is one of the most common and malignant brain tumors in adulthood with a median survival of only 15 months. This poor prognosis is related to GBM’s ability to extensively infiltrate the surrounding brain parenchyma resulting in diffuse spread of neoplastic cells in the brain, responsible for high rate of recurrence. CD44 (Cluster of Differentiation 44) is a transmembrane protein, overexpressed in multiple cancer types, including gliomas, and implicated in cell motility, proliferation and angiogenesis. Multiple studies have investigated the role of CD44 in GBM cells and have highlighted a link between tumor malignancy and CD44 expression. However up to date, little is known of the role of CD44 on cells from the tumor microenvironment (TME). Here, we have investigated a potential role of CD44 in the TME in regards to GBM invasiveness. Using an ex-vivo organotypic brain slice invasion assay, we show that absence of CD44 from the TME impairs the ability of glioma cells to invade the surrounding brain parenchyma. By deleting CD44 in the astrocytic, endothelial and myeloid compartments, we show that it is specifically CD44 expression in myeloid cells that is responsible for the observed phenotype. Combining in vivo studies in cell-specific knock-out mice and in vitro analyses on primary microglia we demonstrate that myeloid CD44 is implicated in Toll Like Receptor 2 signaling and is a major regulator of Matrix metalloproteinase 9 expression.